Characteristics of purpose and quality of speech in Belarusian phraseology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article presents semantic analysis of the sample group of phraseological units of the Belarusian language that constitute two phrase-semantic microfields –«purpose of speech» and «evaluation of the quality of speech». The study made it possible to identify 11 groups of phraseological units within the former and 6 groups within the latter microfield, basing on the previously determined criteria for evaluation of the quality of speech. The study highlights the national and cultural specific information that stresses the negative experience of communication among the Belarusians.
Keywords: phraseological unit; speech; purpose; evaluation of the quality of speech; criteria for evaluation